2019
DOI: 10.1186/s12957-019-1618-4
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal carcinomatosis index predicts survival in colorectal patients undergoing HIPEC using oxaliplatin: a retrospective single-arm cohort study

Abstract: Background Peritoneal carcinomatosis (PC) from colorectal cancer is associated with poor prognosis. Cytoreductive surgery (CRS) combined with hyperthermic intraperitoneal chemotherapy (HIPEC) has improved survival for patients with colorectal peritoneal carcinomatosis. However, standardization of HIPEC protocols, including which chemotherapeutic agent to use, is lacking in the literature. Therefore, we sought to report survival outcomes from colorectal cancer patients undergoing CRS/oxaliplatin-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…There was no statistically significant relationship between KRAS status and the median survival. In contrast, four other more recent multicentre studies have found shorter survival in MT-KRAS tumours in which CRS/HIPEC was performed [ 18 , 23 25 ]. Morgan et al [ 23 ] analysed the value of KRAS mutation in 47 patients undergoing CRS/HIPEC.…”
Section: Discussionmentioning
confidence: 88%
“…There was no statistically significant relationship between KRAS status and the median survival. In contrast, four other more recent multicentre studies have found shorter survival in MT-KRAS tumours in which CRS/HIPEC was performed [ 18 , 23 25 ]. Morgan et al [ 23 ] analysed the value of KRAS mutation in 47 patients undergoing CRS/HIPEC.…”
Section: Discussionmentioning
confidence: 88%
“…A summary of patient characteristics from the studies is shown in Table 1. 9 ,22–46 The median patient age in the studies ( n = 22) ranged from 44 to 62 years. Eight studies reported having patients younger than 20 years of age, and 13 studies reported having patients older than 75.…”
Section: Resultsmentioning
confidence: 99%
“…HIPEC treatment details are available in Table 2. 9,22–46 Treatment protocols in the studies varied, specifically with regard to the timing of the procedure, administration methodology, as well as the therapeutics agent(s) used. The definition of complete cytoreduction (CC) also varied among studies, including CC0 (generally CC0 indicates that no macroscopic peritoneal tumor remains following cytoreduction) and R0 (R refers to resection status; R0 is complete resection) as well as CC1, R1, and/or R2a (classified as CC1 or R2a when tumor nodules less than 2.5 mm persist following cytoreduction; R1 = no macroscopic residual tumor).…”
Section: Resultsmentioning
confidence: 99%
“…HIPEC is one of the most recent treatments enabling a significantly improved survival of the patients. It consists in a local application of a high concentration of warmed anticancer Pt-metallodrugs, such as oxaliplatin, through the peritoneal cavity [28][29][30][31]. In treated women, the intra peritoneal location of ovaries raises the possibility for their contamination with the Pt-drug [13].…”
Section: Introductionmentioning
confidence: 99%